FABRIKASI FOTORESEPTOR BERBASIS LAPISAN IPIS A-SI:H DAN PADUANNYA DENGAN REAKTOR PECVD GANDA - Kade Suardana, I
Abstrack Photoreceptor devices have been fabricated for positive corona in multilayered structure of glass/ZnO /i-a-SiC:H /i-a-Si:H /p-a-Si:H /AI by using dual chamber plasma enhanced chemical vapor deposition (PECVD ) method. 10% Silane (SiH4) and diborane (B2H6) gases diluted in hydrogen (H2) and 100% methane (CH4) gas were used as source gases. As the top passivation layer, the i-type of a-SiC:H with optical band-gap of 2.93 eV were obtained using the CH4 gas fraction of 40%. This highest optical band-gap was chosen to allow more illumination to the photoconductive layer. The optical bang-gap of a-Si:H films of itype varies from 1.7 eV to 1.78 eV. The film of 1.78 eV obtained at the SiH4 gas flow rate of 70 sccm was then used as the photoconductive layer. The a-Si:H films of p-type is also studied in terms of its conductivity. The dark-conductivity of a-Si:H of p-type is relatively constant, varied from 9.11x10\'\"Scm\'\'to 1.75x10\'11Scm The p-type of a-Si:H film with the lowest dark conductivity was then used as the bottom blocking layer to prevent charge injection from photoconductive layer to the conductive electrode. The device obtained shows surface voltage characteristic. It decays as a function of time, with the maximum surface voltage applied is of 50 volts.